Influência da carbodiimida n-(3-dimethylaminopropyl)- N’ethylcarbodiimide hydrochloride (edc) e n,n’- dicicloesilcarbodiimmide (dcc) sobre a resistência de união na interface adesiva em dentina radicular. - Morais, Nathaly Dias (2017)
The main goal of this work was to evaluate the influence of 2 cross-linkers irrigator substances: N-(3-Dimethylaminopropyl)-N’-ethylcarbodiimide hydrochloride (EDC) and N,N´- Dicicloesilcabodiimmida (DCC), over the union resistance over the radicular dentine’s adhesive interface through a push-out test. Sixty (60) monoradicular human teeth were extracted, and then divided in 2 groups, being the first group referred to as initial time (T0), and the second one as post-thermocyclage (TH). These 2 groups were then divided into 3 subgroups each: T0 (Control: 10 teeth; EDC: 10 teeth; DCC: 10 teeth) and TH (Control: 10 teeth; EDC: 10 teeth; DCC: 10 teeth). The push-out test was realized and the results were submitted to a variance analysis. The statistical inference was realized after the treatment of the data collected through T-student test and ANOVA with Tukey’s parity, with all tests having 5% significance level (α=0,05). For the T0 subgroups, the results showed that there isn’t difference between the means, however, in the TH subgroups the use of DCC resulted in a larger than average mean of the pine-to-teeth union resistance. In a comparison between the T0 and TH groups there were no difference between the observed means on DCC application. It was concluded that the cross-linkers did not affected the union resistance, on the other hand, the DCC despite not improving union resistance, kept the stability in the dentine-to-pine interface